Symbol timing synchronization in software radio receivers - DOYLE, LINDA; NOLAN, KEITH; O'MAHONY, DONAL (My University, 2004)
The Centre for Telecommunications Value Chain Driven Research (CTVR) approach to software radio is to focus on the use of a general-purpose processor (GPP). The use of a GPP to perform signal processing for communications applications presents the developer with challenges but it also presents some opportunities. We argue new classes of algorithms are required which will exploit the advantages and negate the disadvantages of using a GPP. Indeed other researchers have already started this programme of `algorithmic advances?. This paper discusses the issues involved and reviews some existing developments. We present our own progress in developing a noise adaptive symbol synchroniser and we discuss some initial thoughts on how these techniques may be applied to radio functions generally.
Proceedings of the SDR 04 Technical Conference and Product Exposition
Software Defined Radio Technical Conference and Product Exposition
PUBLISHED
Phoenix, Arizona
Keywords: Electronic & Electrical Engineering